HUBUNGAN LANGSUNG DAN TIDAK LANGSUNG TINGKAT PEMAHAMAN DAN PARTISIPASI PENGGUNA TERHADAP KEPUASAN PENGGUNA DALAM PENGEMBANGAN SISTEM INFORMASI (Studi terhadap Pengguna dalam Industri Perbankan) - Priyo Hari Adi; Susetyo Rini (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2006)
Research in end users of the information system development found the importance of involving the user to participate in order to get the system success. Some research concluded that user participation influenced the system success significantly. However, there are so many questions of the extension of the study. The objective of the study is to examine the direct and indirect effect of the user participation to the user satisfaction in information system development. The study also intended to examine how the user understanding influences the user participation and user acceptance in order to get the user satisfaction. Based on these objectives, this study uses the comprehensive model called Structural Equation Modeling (SEM). The study especially involves the respondents from the banking industries. That is the reason why it used the term of user understanding rather than user expertise. Most of the users are in the implementation stage of the system development that needs the understanding rather than the expertise to operate the system. The result is the user understanding significantly influenced the user acceptance and the user participation. The study also concludes that the user acceptance significantly influenced the user satisfaction. In the context of indirect effects, the study recommends to raise the user acceptance in order to get the user satisfaction by raising the user understanding in the information system development.Keywords : user understanding, user participation, user acceptance dan user satisfaction, information system development